DESAIN INSTALASI PENGOLAHAN AIR LIMBAH RSUD SALATIGA - Novianti Mandasari (Jurnal Teknik Lingkungan, 2012)
RSUD Salatiga is a hospital that already has a wastewater treatment plant, but has not been able to process all the waste generated. Wastewater treatment plant will be designed to process wastewater from the installation of nutrition, laundry, PONEK, pavilion and classroom III. WWTP capacity will be made at 120.4 m3/day with the type of anaerobic-aerobic biofilter treatment. Processing to be used consists of control boxes, tubs fat separator, equalization basin, tub anaerobic decomposition, initial deposition basin, anoxic biofilter, biofilter aerobic, final settling basin and bath indicators with the disinfection process. Later, when the new WWTP has been made, the existing WWTP will be retained so that the hospital will have two WWTP Salatiga.